(3GdYed HGdcQI GdadcjIs - (3bSWG Hf dhbG GdHYdHcj,J (B300 (3g` s
(3ChdgG (B:s
(3bGd (B: (3cd aGVd Gddg aeMHJg hGLHI aGJNPJ dc (B_ (3CYRc Gddg (B_ (3cQI eYehdI Ydi UhQI Gdadc eHfi Ydi NdbI GdSeGA s
(3BNQgG (B:s
(3aMjK GfJgi YOOc ef CLRGA MdbI fUa GdffgGQ aYO eG Hjf GdYdGeJjf ef GdCLRGA aeG NQL dc agi CLRGA ejd Pdc GdchcH Yf SeJ GdQCS fLR hHGddg GdJhajb s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3cJHJ Hbde ajg VHWs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B196 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B131s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B222 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B365 s
Keywords: (3Gdadcs